2018
DOI: 10.1111/are.13799
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the effect of dietary prebiotics and probiotics on gut bacterial richness and diversity of Asian snakehead fingerlings using T-RFLP method

Abstract: This study was designed to evaluate the effects of three prebiotics (β-glucan, galacto-oligosaccharide [GOS], mannan-oligosaccharide [MOS]) and two probiotics (Saccharomyces cerevisiae, Lactobacillus acidophilus) on the microbiome of snakehead during growth of fingerlings. In addition, the experiment evaluated the capacity of Channa striata fingerlings to retain the benefits derived from these supplements after withdrawal. Throughout the study, it was observed that supplementation with dietary prebiotics and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In the present study, intestinal modulation through bacterial colonization and changes in intestinal morphology explain the superior performance. The presence of probiotic bacteria in the intestinal tract during an unbroken feed period promotes the growth of villi and consequently greater nutrient absorption (Sayes et al, 2017;Munir et al, 2018). Thus, higher weight gain or better specific growth rate represent some of the benefits of autochthonous bacteria that have been reported in the literature and observed in clownfish.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, intestinal modulation through bacterial colonization and changes in intestinal morphology explain the superior performance. The presence of probiotic bacteria in the intestinal tract during an unbroken feed period promotes the growth of villi and consequently greater nutrient absorption (Sayes et al, 2017;Munir et al, 2018). Thus, higher weight gain or better specific growth rate represent some of the benefits of autochthonous bacteria that have been reported in the literature and observed in clownfish.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that probiotics boosted growth, enzymatic contribution to nutrition, suppression of adhesion and colonization of harmful bacteria in the digestive tract, regulation of the gut microbiota and increased haematological parameters and immunological response of shellfish (Ringø, 2020). Dietary probiotics ( Saccharomyces cerevisiae , Lactobacillus acidophilus ) supplementation resulted in a significant improvement in the gut microbial profile and improvement in gut morphology of Asian snakehead ( Channa striata ) fingerlings (Munir et al, 2018). Probiotics added to water during the early stages of growth had the most beneficial effects in the survival of yellow perch, Perca flavescens (Shaheen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary probiotics are considered as a bioremediation and environmental friendly tool for the aquaculture development and sustainability (Ahmad et al, 2017; Eissa et al, 2022; Zibiene & Zibas, 2019), as they have proven to be a great substitute for antibiotics developing the beneficial microflora in the digestive truck of the fish (Huerta‐Rábago et al, 2019; Kavitha et al, 2018; Mamun et al, 2019; Munir, Terence, et al, 2018; Wang et al, 2020). Therefore, fish fed with dietary probiotic supplement exhibited the enhancement of growth performance and health status of several studied fishes like Malaysian mahseer (Sharifah Lia et al, 2022), Asian snakehead (Munir, Roshada, Abdul‐Manaf, & Azizah, 2016; Munir, Roshada, et al, 2018; Munir, Roshada, Yam, et al, 2016; Munir, Terence, et al, 2018; Talpur et al, 2014), common carp and grass carp (Sahandi et al, 2012), tilapia fish (Mohamed et al, 2013).…”
Section: Introductionmentioning
confidence: 99%